Evaluation of life quality of patients undergoing surgical treatment for rectal cancer in bearing of socio-demographic factors - Ponczek, Danuta; Nowicki, Andrzej; Zegarski, Wojciech; Banaszkiewicz, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2006)
Objective: The aim of the work was an assessment of the influence of socio-demographic factors on the long-term quality of life in patients who underwent low anterior resection or abdominoperineal resection with no preoperative radiation therapy, because of colorectal cancer. Material and methods: Based on the analysis of medical records of 481 patients with colorectal cancer a selection of patients eligible for the study was made. Conclusively, 102 patients were included in the study. 102 questionnaires were distributed by post. 78 patients returned the questionnaires (76.5 proc.). Data was collected using a QLQ-C30 questionnaire for assessment of quality of life in cancer patients and a colorectal cancer module QLQ-CR38. Additionally a questionnaire of socio-demographic factors such as: age, gender, education, place of residence, material status, family relations, support, coexisting diseases, complementary and alternative treatment and length of time after operation was used. Results: The men have shown a better health condition, better physical, emotional and social activity than women. Women have more health problems than men, such as fatigue, vomiting, nausea, pain and constipation. The gender has significant statistical influence on sexual functionality. Men got higher value that women so their sexual activity was better. Conclusions: Socio-demographic factors significantly influence the quality of life in patients after colorectal cancer operation. The following factors had positive influence the quality of life after operation: gender (male), age (46-55), higher education, good and sufficient material status, family, lack of coexisting diseases, family support and long time after operation.